THE INFLUENCE OF SERVICE QUALITY ON COMMUNITY SATISFACTION IN THE MAKING OF E-KTP IN LUMAJANG REGENCY - Tomy Ernawati; Suwignyo Widagdo; Yuniorita Indah Handayani (STIE Mandala Jember, 2021)
This study aims to determine the quality of services to community satisfaction for making EKTP in Sumbersuko District, Lumajang Regency. This research was conducted in SumbersukoDistrict, Lumajang Regency. The population in this study is the people in SumbersukoSubdistrict who already have E-KTP with totaling 27,306 people. The sampling method usessimple random sampling with questionnaire distribution techniques. The number of samples inthis study was 125 respondents spread in Sumbersuko District. The method of data analysis inthis study used multiple linear regression analysis with the help of SPSS 20.0 software. Based onthe results of data analysis shows that the variable responsiveness, assurance, and empathy havea significant effect on community satisfaction with the value of the influence of respectively27.3%, 30.5%, and 14.3%. While the tangible and reliability variables did not significantlyinfluence community satisfaction in making E-KTP in Sumbersuko District, Lumajang Regency.This result also shows that the assurance variable is the most dominant variable influencingcommunity satisfaction in making E-KTP in Sumbersuko District, Lumajang Regency.Keyword: Service Quality, Community Satisfaction, E-KTP